Design and build prototype of automatic curtain moving system - Kapitány, Pálma (Design of Machines and Structures, 2024)
The paper deals with an automatic curtain moving system. Here shown the pro-cess of design and build prototype. Solution of problem included design of mechanical construction, electric circuit and program of control. Nowadays is so popular to build houses by sandwich panel. This building method allows quick and modular process of building of halls. In this paper found a possible way for also quick and modular automatic curtain moving system. Chapters deal with initial known and added parameters and the problem. Furthermore, paper says about curtain cornice solutions, sliding ways, design of sheet metal components, DC motor choice, microcontroller and communication preparing. At the end found the conclusion of first prototype.